2010
DOI: 10.1159/000282667
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and Radical Oxygen Species Are Involved in Microvascular Effects of Hyperoxia

Abstract: Hyperoxia causes vasoconstriction in most tissues, by mechanisms that are not fully understood. We investigated microvascular effects of breathing 100% oxygen in healthy volunteers, using iontophoresis to deliver acetylcholine (ACh) and sodium nitroprusside (SNP). Aspirin and vitamin C were used to test for involvement of prostaglandins and radical oxygen species. Forearm skin perfusion was measured using laser Doppler perfusion imaging. Results were analysed using dose-response modelling. The response to ACh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 89 publications
2
31
0
1
Order By: Relevance
“…The perfusion reduction effect of the oxygen supplementation has been known for several years, and is thought to be attributed not to sympathetic stimulation [26,27] but rather to the reactive oxygen species (ROS)-mediated inhibition of vasodilator prostanoid synthesis. [28] As expected, during oxygen breathing in the provocation phase, tc-pO 2 increased significantly, saturating hemoglobin and increasing its amount dissolved in plasma, thereby creating hyperoxia. In response to this increase, a vasoconstriction seemed to have occurred, which led to the statistically significant reduction of mbf.…”
Section: Resultssupporting
confidence: 60%
“…The perfusion reduction effect of the oxygen supplementation has been known for several years, and is thought to be attributed not to sympathetic stimulation [26,27] but rather to the reactive oxygen species (ROS)-mediated inhibition of vasodilator prostanoid synthesis. [28] As expected, during oxygen breathing in the provocation phase, tc-pO 2 increased significantly, saturating hemoglobin and increasing its amount dissolved in plasma, thereby creating hyperoxia. In response to this increase, a vasoconstriction seemed to have occurred, which led to the statistically significant reduction of mbf.…”
Section: Resultssupporting
confidence: 60%
“…These effects make assessment of vasoconstrictor responses difficult to perform using laser Doppler based perfusion detectors. (Rousseau et al, 2010). …”
Section: Vasoconstrictionmentioning
confidence: 99%
“…Despite conflicting evidence regarding the mechanisms by which the drug causes vasodilatation, ACh is commonly delivered iontophoretically to test endothelial function in a variety of clinical conditions, including diabetes (Arora et al, 1998;Cohen et al, 2008;Hannemann et al, 2002;Morris et al, 1995) , hypertension (Cupisti et al, 2000b;Farkas et al, 2004;Kellogg et al, 1998;Monostori et al, 2010), pre-eclampsia (Blaauw et al, 2005;Eneroth-Grimfors et al, 1993;Khan et al, 2005), Raynauds phenomenon (Anderson et al, 1996;Hettema et al, 2009;Khan and Belch, 1999), renal failure (Cupisti et al, 2000a), HIV (Monsuez et al, 2000) and heart failure (Andersson et al, 2005;Balmain et al, 2007). Also, it has been applied to investigate the effects of smoking (Pellaton et al, 2002), age (Rossi et al, 2002a), gender (Algotsson et al, 1995), hyperoxia (Rousseau et al, 2010;Yamazaki, 2007) and exercise (Lenasi and Strucl, 2004;Rossi et al, 2002b). …”
Section: Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of this effect, no statistical differences between parameters were found when the volunteer was breathing room air or oxygen, indicating that the MN-induced vasodilation mechanisms overpassed the hyperoxia-mediated blood flow reduction mechanisms. Recent studies reported different effects of hyperoxia on skin vasodilation mediated by different drugs [15,16] . However, none of these studies involved the application of MN.…”
Section: Resultsmentioning
confidence: 99%